2016
DOI: 10.1074/jbc.m116.754622
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Factor VIII Forms a Bivalent Complex with the Low Density Lipoprotein (LDL) Receptor-related Protein 1 (LRP1)

Abstract: Hemophilia A is a bleeding disorder caused by a deficiency in coagulation factor VIII (fVIII) that affects 1 in 5,000 males. Current prophylactic replacement therapy, although effective, is difficult to maintain due to the cost and frequency of injections. Hepatic clearance of fVIII is mediated by the LDL receptor-related protein 1 (LRP1), a member of the LDL receptor family. Although it is well established that fVIII binds LRP1, the molecular details of this interaction are unclear as most of the studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 52 publications
6
20
1
Order By: Relevance
“…This might be difficult if we consider that the potential residues for LRP1 interaction are oriented towards the center of the C1q cone ( Figure 11). Some LRP1 ligands have been described to interact better with cluster IV than with cluster II which is also what we observe in our study (33,44). From that observation, one could hypothesize that the LRP1 ligands bind first to the cluster that is more distant from the membrane (cluster II) and then interact with cluster IV.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This might be difficult if we consider that the potential residues for LRP1 interaction are oriented towards the center of the C1q cone ( Figure 11). Some LRP1 ligands have been described to interact better with cluster IV than with cluster II which is also what we observe in our study (33,44). From that observation, one could hypothesize that the LRP1 ligands bind first to the cluster that is more distant from the membrane (cluster II) and then interact with cluster IV.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the affinity of the C1r2s2 interaction with C1q is stronger than the one of soluble LRP1 clusters which is in favor of the C1 formation in this experimental setting [ A common feature of most of LDL-receptors ligands is their ability to bind to heparin, suggesting the implication of one or more highly positively charged regions in the recognition of the receptor. Indeed, a "Lysine ligand mode" of interaction with tandem CR modules has been described for the binding of LRP1 with its ligands, such as RAP (30), a2Macroglobulin (31), ApoE (32), and factor VIII (33). These interactions are calcium dependent and salt sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Receptors implicated in FVIII uptake are also present on monocytes/macrophages. 29 For example, LRP1/CD91, an endocytic receptor, has been shown to bind FVIII 30 and was found to be upregulated in monocytes from HemA patients. 31 As rFVIIIFc is administered IV, blood monocytes of HemA patients are the first innate immune cells to interact with the administered FVIII.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we identified cluster II as the sole LRP1 binding site for ricin, and demonstrated that this binding is mediated by subunit B of the toxin. Cluster II and IV, which are responsible for the majority of ligand binding to the LRP1 receptor 40,[57][58][59] are highly similar in their binding properties, displaying only minor differences regarding their kinetics of interactions 60 . Huang et al 61 , suggested that the CR modules within these clusters, present different charge densities and hydrophobic patches, which in turn lead to varying receptor-ligands interactions responsible for the different ligand specificity of each cluster.…”
Section: Discussionmentioning
confidence: 99%